1983
DOI: 10.1111/j.1530-0277.1983.tb05435.x
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo‐Controlled Double‐Blind Comparative Clinical Study of the Disulfiram‐ and Calcium Carbimide‐Acetaldehyde Mediated Ethanol Reactions in Social Drinkers

Abstract: Treatment for 2 days with disulfiram (3.5 mg/kg once daily) and calcium carbimide (0.7 mg/kg twice daily) in social drinkers produced, as compared to controls, similar blood ethanol values, 2- to 3-fold increases in blood acetaldehyde, respectively, and increased heart rate, pulse pressure, skin temperature, and flushing following 0.15 g/kg of ethanol taken 12 hr after the last drug administration. Peak blood acetaldehyde concentration was greater for calcium carbimide compared to disulfiram (p less than 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

1984
1984
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…[162][163][164] After alcohol consumption, both drugs lead to high blood acetaldehyde levels that result in a range of unpleasant effects. 165,166 Although some studies have reported that treatments with ALDH inhibitors effectively reduce alcohol relapse in withdrawn alcoholics, 162 it remains unclear whether their protective effects against alcohol relapse are actually based on the adverse effects induced by acetaldehyde. Instead, the reduction of alcohol consumption in ALDH inhibitors-treated alcoholics might be due to their belief that a harmful and potentially fatal reaction could occur after alcohol drinking.…”
Section: Pharmacological Manipulations Of Ethanol Metabolism In Humansmentioning
confidence: 99%
“…[162][163][164] After alcohol consumption, both drugs lead to high blood acetaldehyde levels that result in a range of unpleasant effects. 165,166 Although some studies have reported that treatments with ALDH inhibitors effectively reduce alcohol relapse in withdrawn alcoholics, 162 it remains unclear whether their protective effects against alcohol relapse are actually based on the adverse effects induced by acetaldehyde. Instead, the reduction of alcohol consumption in ALDH inhibitors-treated alcoholics might be due to their belief that a harmful and potentially fatal reaction could occur after alcohol drinking.…”
Section: Pharmacological Manipulations Of Ethanol Metabolism In Humansmentioning
confidence: 99%
“…Por su parte, la genética humana muestra que la deficiencia en ALDH, concretamente en ALDH 2 * 2 (8, para una reciente revisión), supone una mayor concentración de acetaldehído tras la ingesta de etanol frente a sujetos con ALDH normal (ALDH 2 ) (115), siendo la acumulación de acetaldehído parcialmente responsable de las bajas dosis de etanol consumidas (116,117). También se ha indicado que la presencia de flushing facial tras el consumo de etanol podría contribuir a un menor consumo (118), sin embargo, los datos obtenidos son contradictorios (119,120).…”
Section: Estudios Genéticosunclassified
“…Algunos autores justifican estos resultados planteando que los altos niveles de acetaldehído en sangre, como consecuencia de la inhibición de ALDH (132) son tóxicos y producen efectos aversivos (133). Sin embargo, tras el uso de estos inhibidores también se ha visto que concentraciones de etanol que no tenían ningún efecto en los sujetos, pasan a ser reforzantes cuando se dan tras la administración de un inhibidor de ALDH (120,121,122,123,124,134). Este hecho pone de relieve la implicación de este enzima en los efectos reforzantes del etanol.…”
Section: Estudios Conductualesunclassified